Counterfeiting of HIV/AIDS medicines : implications for global epidemic : recommendations for workplace programs - Norris, Gerard Benedict (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2005.